Meta-analysis of the prognostic value of smad4 immunohistochemistry in various cancers. - Yiping Du; Xin Zhou; Zebo Huang; Tianzhu Qiu; Jian Wang; Wei Zhu; Tongshan Wang; Ping Liu (PLoS ONE, 2014)
Accumulating evidence indicates that Smad4 (DPC4) plays a fundamental role in the development and prognosis of several types of cancer. The objective of this study was to conduct a meta-analysis to evaluate whether the loss of Smad4 staining could serve as a prognostic marker.A comprehensive meta-analysis was conducted using major useful databases to determine the relationship between the immunohistochemical detection of Smad4 and the survival of patients with various cancers. We used hazard ratios (HRs) with 95% confidence interval (CIs) as the effect estimation to evaluate the association of Smad4 with overall survival (OS), cancer-specific survival (CSS) or recurrence-free survival (RFS). The relationship between the clinical characteristics of patients and Smad4 was also evaluated using the odds ratio (OR).A total of 7570 patients from 26 studies were included in the analysis. The pooled results showed that loss of Smad4 staining was a negative predictor of OS with an HR of 1.97 (95% CI: 1.55-2.51; Pheterogeneity<0.001) and CSS/RFS (HR = 1.81; 95% CI: 1.30-2.54; Pheterogeneity<0.001). In addition, loss of Smad4 staining was more likely to be found in older (OR = 1.69, 95% CI: 1.09-2.61; Pheterogeneity = 0.648) colorectal cancer patients with a late tumor stage (OR = 2.31, 95% CI: 1.71-3.10; Pheterogeneity = 0.218) and in gastric cancer patients with lymph node metastasis (OR = 2.11, 95% CI: 1.03-4.34; Pheterogeneity = 0.038).Based on these results, our meta-analysis provided evidence that loss of Smad4 staining could act as an unfavorable biomarker in the prognosis of various cancers and should be used as a powerful tool in future clinical trials.